PENGARUH KOMPETENSI, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU SMKN 1 SITUBONDO MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Heliyana, Eni; Pramesthi, Riska Ayu; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Educational institutions are essential for the progress of the nation's civilization; for this reason, SMKN 1 Situbondo has a vital role in producing superior Indonesian human resources. SMKN 1 Situbondo graduates must become competitive and have superior human resources. This study aimed to analyze and test the effect of competence, work discipline, and work environment on the performance of SMKN 1 Situbondo teachers through work motivation. This research is explanatory; the population in the study consisted of ASN teachers of SMKN 1 Situbondo. The sampling technique was determined by quota sampling. The study's data analysis and hypothesis testing used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that Competence has a negative but insignificant effect on work motivation, work discipline has a positive but insignificant effect on work motivation, work environment has a significant positive effect on work motivation, competence has a positive but insignificant effect on teacher performance, work discipline has a significant positive effect on teacher performance, work environment has a negative but insignificant effect on performance, work motivation has a significant positive effect on teacher performance. The results of indirect effect hypothesis testing show that competency variables have a negative but insignificant effect on teacher performance, work discipline has a positive but insignificant effect on teacher performance, and work environment has a significant positive effect on teacher performance.